Mind the Rhythm: ECG QT Dispersion and Cognition in Healthy Older Adults - Vrinceanu, Tudor; Lagacé-Lavoie, Geneviève; Kaushal, Navin; Esmail, Alida; Vu, T. T. Minh; Berryman, Nicolas; Nigam, Anil; Bherer, Louis (Frontiers in Psychology, 2020)
Background: Autonomic function has been linked to cognitive abilities in aging. Even in non-clinical states, a certain variability in heart rhythm regulation can be measured with QT dispersion (QTcD), an ECG marker of ventricular repolarization which has been linked to autonomic function and cardiovascular health. QTcD has been shown to be higher in individuals with mild cognitive impairment, and the highest in individuals with Alzheimer’s disease. The goal of this study was to see if QTcD is associated with cognitive performance in healthy individuals. Methods: Sixty-three healthy inactive older adults (> 60 years) completed an extensive cognitive assessment (including inhibition, divided attention, updating, working memory, and processing speed), a physical fitness assessment, and underwent a resting ECG. Results: After controlling for age, sex, and education, QTcD significantly predicted global cognition (MoCA) scores (R2 = .17, F(4.58) = 3.00, p < .03, β = -.36). Exploratory analysis on the MoCA subcomponents revealed a significant association between the visual/executive subcomponent and QTcD (R2 = .12, F(1.61) = 7.99, p < .01, β = -.34). In individuals with high QTcD, QTcD values were linked to executive functions (R2 = .37), processing speed (R2 = .34), and dual-task performances (R2 = .47). No significant associations were found within the low QTcD group. Conclusion: This study shows an association between ventricular repolarization (QTcD) and cognitive performance, in particular speed of processing and executive functions, in healthy older adults. The results provide further support for linking autonomic heart regulation and age-related cognitive changes, and suggest that deviations on ECG, even within-normal range, could help detect early cognitive deficits.